Exposing an “Intangible” Cognitive Skill Among Collegiate Football Players: II. Enhanced Response Impulse Control - Bashore, Theodore R.; Ally, Brandon; van Wouwe, Nelleke C.; Neimat, Joseph S.; van den Wildenberg, Wery P. M.; Wylie, Scott A. (Frontiers in Psychology, 2018)
American football is played in a dynamic environment that places considerable demands on a player’s ability to make fast, precise reactions while controlling premature, impulsive reactions to spatial misinformation. We investigated the hypothesis that collegiate football players are more proficient than their non-athlete counterparts at controlling impulsive motor actions. National Collegiate Athletic Association (NCAA) Division I football players (n=280) and non-athlete controls (n=32) completed a variant of the Simon conflict task, which quantifies choice reaction speed and the proficiency of controlling spatially-driven response impulses. Overall, the choice reaction times and accuracy rates of football players and controls were equivalent. Similarly, football players and controls were equally susceptible to producing incorrect impulsive motor responses. However, the slowing of reaction time attributed to the activation and successful inhibition of these impulses (i.e., the Simon effect) was reduced significantly among football players compared to controls. Moreover, differences in impulse control varied by position among the players, with the reduction being greater for offensive than for defensive players. Among offensive players, running backs, wide receivers, and offensive linemen had greater impulse control than did controls, whereas among defensive players only linebackers had greater control. Notably, the Simon effect was reduced by 60% in running backs compared to controls. These results contribute to emerging evidence that elite football players possess more proficient executive control over their motor systems than their age counterparts and suggest that the speed of controlling impulsive motor reactions may represent an enhanced cognitive “intangible” among football players.